Research on the Concept and Ownership Issues of Data Assets - Zhang, Yuhan (Asia Pacific Economic and Management Review, 2026)
The digital economy's rapid growth has made data a key driver of economic and social development. However, the replicable and shareable nature of data assets complicates the clear definition of ownership, hindering efficient circulation, market allocation, and technological innovation. Defining data ownership involves balancing the interests of multiple stakeholders—individuals, businesses, and governments—amid challenges such as non-exclusivity and replication. Current legal frameworks, including China's Data Security Law and Personal Information Protection Law, remain inadequate in addressing these issues systematically, while international disagreements over data sovereignty add further complexity. This study examines theoretical and practical challenges related to data asset ownership and proposes an ownership framework aimed at balancing efficiency and fairness. Theoretically, it explores innovations in data property rights and accounting standards. Practically, it analyzes ownership disputes between individuals and enterprises, offering insights for improving data infrastructure, facilitating data circulation, and reconciling individual rights with public interests.